Exploration and Analysis of Factors Influencing Group Learning - Zhao, Jianhua; McConnell, David (Proceedings of the International Conference on Networked Learning, 2004)
The purpose of this paper is to explore which factors influence group learning content, and content analysis is chosen as the research method. The sample for this study is the literature on group learning. 35 books and 1 paper are examined. The coding system for the content analysis is an opened and a self-expanded system in this study, which means that the original coding system can be updated if the new coding item is developed during the data collection. A total of 62 influencing factors are identified in terms of the content analysis. In order to organise them systematically, we categorised them into four aggregations according to one model of the group learning processes: planning, organising, learning process, and evaluation. The result of this study may be used to design a questionnaire and to model group learning process in our further research.